THE PAPER CHARACTERISTICS FROM COMBINATION OF RICE HUSKS AND EMPTY FRUIT BUNCHES - Yuli Ristianingsih; Hero Islami; Muhammad Sarwani (Universitas Lambung Mangkurat, 2017)
Abstract- Rice husk and empty fruit bunches are agricultural and plantation wastes which have fiber cellulose and hemicellulose, it can be converted to pulp and paper. This research aims to study the effect of NaOH concentration (2, 4, 6 and 8% w/v) and raw material composition to pulp yield and to study characteristics of the paper combination of rice husk and empty fruit bunches using soda process based on SEM and XRD analysis. This research using soda process because it is suitable for non-wood raw materials, low cost operations and not use sulfur compounds. Dry raw materials are mixed with NaOH and digesting using autoclave (100°C, 1 atm) for 60 minutes. NaOH concentration optimum used in the pulping process a combination rice husk and empty fruit bunches (1:3, 1:2, 1:1, 2:1 and 3:1) and then cooled for 30 minutes. Pulp is bleached with NaClO 5.25% (v / v), then formed and dried as paper. The lowest pulp yield obtained in a ratio of 2: 1 is 27.6%. Based on the observation of SEM known the fiber of rice husk and empty fruit bunches is 5.88 to 9.8 μm and 8.82 to 14.71 μm, while based on XRD observations, chemical treatment can improve the characteristic of peak intensity on paper combination. The highest advances of peak intensity in the 1:3 ratio is 71.28% (cellulose I) dan 83.33% (cellulose II). Keywords: rice husk, empty fruit bunches, chemical pulping, soda process